(untitled) (Veterinary Science, 2024)
The objective of this work was to evaluate the forage quality of goat intake in an establishment in the department of Limay Mahuida, La Pampa, at different times of the year, together with hematological parameters and serum levels of minerals of grazing goats. To do this, temporary ingestion was simulated using the results of previously carried out work as a basis. Five simulations were carried out per station and in each of them the content of crude protein (CP), neutral detergent fiber (NDF) and acid detergent fiber (ADF), dry matter (DM) basis, was analyzed. The quality of drinking water was also evaluated. In each season of the year, blood samples were taken from 15 adult goats to determine hematological variables and serum concentration of calcium (Ca), phosphorus (P), magnesium (Mg), copper (Cu) and free T4 (T4 L). The lowest ADF concentration (34.5%) corresponded to spring. The highest levels of CP intake were observed in winter and spring. The average values in drinking water were 4,764 mg of total salts/l, sulfates: 1,662 mg/l, Ca: 659 mg/l and (sodium) Na: 437 mg/l. With respect to minerals in serum, lower levels of P and higher levels of Cu can be highlighted in summer and lower concentrations of Mg in autumn and spring, but without indicating situations of mineral deficiency. It can be concluded that the goat intake, allowed the requirements in the different physiological stages to be covered.